Pre-assumption and Implicature of Stand Up Comedy Indonesia (Season 10) and its Relation to Anecdote Texts - Sulistyono, Yunus; AnurAdha, Bryan Braga Widya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This descriptive qualitative research aims to: (1) describe the types of presuppositions that appear in the humor of Stand Up Comedy Indonesia Season Ten; (2) describe the implicatures contained in the material performed by the participants; and (3) explain the relevance of the analysis of presuppositions and implicatures to teaching anecdotal texts in Indonesian language learning at the high school level. Methodology: The data consisted of speech material from participants who achieved the highest positions from the first to the final round. The data source was the Kompas TV Stand Up YouTube channel, which was downloaded for analysis. Data were collected through listening and note-taking techniques. The data were then categorized and identified based on types of presupposition and implicature using the respective linguistic theories. Results: The study found that the most frequently occurring presuppositions were existential presuppositions and counterfactual presuppositions. The most common type of implicature identified was general conversational implicature, which was used to make it easier for the audience to understand the intended meaning. Applications/Originality/Value: The results of this study are relevant for teaching anecdotal texts in high school Indonesian language classes. By incorporating stand-up comedy material, learning becomes more engaging, imaginative, and conducive to helping students express their ideas and thoughts creatively.